Trafficking of the telomerase RNA using a novel genetic approach - Jessica K. Day; Brett J. Palmero; Amanda L. Allred; Junya Li; Fatima B. Hooda; Graeme Witte; Alexandra M. Dejneka; Anna M. Sandler; Karen E. Kirk (PLoS ONE, 2025)
Telomeres are specialized nucleoprotein structures situated at eukaryotic chromosome ends, vital for preserving genetic information during cell replication. Telomerase, a holoenzyme composed of telomerase reverse transcriptase and an RNA template component, is responsible for elongating telomeric DNA. The intracellular trafficking of the telomerase RNA (TER) varies, either staying in the nucleus or exiting to the cytoplasm, depending on the organism. For example, in Saccharomyces cerevisiae , the RNA template is exported to the cytoplasm, whereas in mammalian cells and protozoa, it remains within the nucleus. Aspergillus nidulans , a filamentous fungus, offers an outstanding model for investigating telomeres and telomerase due to its characterized telomerase components, exceptionally short and tightly regulated telomeres, and innovative heterokaryon rescue technique. To determine the pathway of telomerase RNA trafficking in A. nidulans , we leveraged its unique capabilities to exist in both uni- and multi-nucleate states within a heterokaryon. This involved creating a TER knockout A. nidulans strain ( TERΔ ) and examining the resulting colonies for signs of heterokaryon formation. Heterokaryons would imply the export of TER from one nucleus and its import into a TERΔ nucleus. Interestingly, the TERΔ strain consistently failed to produce heterokaryons, instead giving rise to likely diploid colonies. This surprising finding strongly implies that telomerase assembly predominantly takes place within the nucleus of A. nidulans , distinguishing it from the biogenesis and trafficking pattern observed in yeast.